answer : 1/6
start from the top equation first -
1/2 + 1/2 (simplified) - 5/6
1 - 5/6 = 1/6
bottom eq. -
3/2 x 1/3 = (times top by top, bottom by bottom) 3/6 = 1/2
1/2 divided by 5/10
1/2 divided by 1/2
(flip the second fraction and multiply instead of dividing)
1/2 x 2/1 = 2/2 = 1
final eq. 1/6 divided by 1 = 1/6
=)
2007-06-11 20:25:43
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Let us do the numerator and denominator separately.
Numerator:
1/2 + 2/4 - 5/6 = (6 + 6 - 10) / 12 = 2/12 = 1/6
Denominator:
3/2 x 1/3 / (5/10)
3/2 x 1/3 = 1/2
5/10 = 1/2
Dividing with 1/2 is same as multiplying by 2/1
So, 1/2 x 2/1 = 1
So the denominator is 1.
anything divided by 1 remains unaffected.
So the answer to your question is
1/6 divided by 1 = 1/6
2007-06-11 20:48:57
·
answer #2
·
answered by Swamy 7
·
0⤊
0⤋
It would be correct to put it as (1/2+2/4-5/6)/(3/2x1/3 divided by 5/10). So we would work the math in both parenthesis first. 1/2+2/4 = 2/4+2/4=1 ; 1-5/6 = 6/6-5/6 = 1/6 so the top = 1/6 Now the bottom would be 3/2x1/3=3/6=1/2; 1/2 divided by 5/10 = 1/2 x 10/5=10/10=1
So any number divided by 1 is equal to itself.
The answer is 1/6
2007-06-11 20:34:07
·
answer #3
·
answered by William S 1
·
0⤊
0⤋
1/2+2/4-5/6= 1/6
3/2 x 1/3 is 1/2 divided by 5/10= 1
2007-06-11 20:31:47
·
answer #4
·
answered by ♥♥Pro♥♥ 6
·
0⤊
0⤋
1/2 + 2/4 - 5/6
= 3/6 + 3/6 - 5/6
= 6/6 - 5/6
= 1/6
3/2 x 1/3 / 5/10
= 3/6 / 5/10
= 15/15
= 1
1/6 divided by 1
= 1/6
answer is: 1/6
2007-06-11 20:29:44
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
1/2 +2/4 - 5/6
------------------
3/2 x 1/3 divided by 5/10
first 12 is lcd
6/12 + 6/12-10/12=2/12=1/6
3/2 x 1/3=3/6=1/2 divided by 5/10= 1/2 x 10/5=2 1/2 x 2=1
1/6 divided by 1= 1/6
2007-06-12 02:00:08
·
answer #6
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
1/2 + 2/4 -5/6 / 3/2 x 1/3 / 5/10
start with the denominator
3/2 x 1/3 / 5/10 = 3/2 x 1/3 x 10/5= 3/6 x 10/5 =30/30 = 1
now the numerator
1/2 + 2/4 - 5/6 = 1 -5/6 = 1/6
1/6 / 1 = 1/6
2007-06-11 20:30:13
·
answer #7
·
answered by kale_ewart 5
·
0⤊
0⤋
1/2 + 2/4 = 1
minus 5/6 = 1/6 for the numerator
3/2 x 1/3 = 1/2 times 10/5 = 1
1/6 divided by 1
you've got it from here (I hope)
best of luck - why aren't you in bed!?
2007-06-11 20:27:15
·
answer #8
·
answered by tom4bucs 7
·
1⤊
0⤋
Numerator (N)
1/2 + 1/2 - 5/6
= 1 - 5/6
= 1/6
Denominator (D)
= (3/2) x (1/3) / (5/10)
= (3/2) x (1/3) x (10/5)
= (1/2) x (10/5)
= 5 / 5
= 1
N/D = 1/6
2007-06-11 22:33:14
·
answer #9
·
answered by Como 7
·
0⤊
0⤋
1/2 + 2/4 - 5/6
=(6+6-10)/12
=2/12
=1/6
(3/2 * 1/3) / (5/10)
=1/2 / (5/10)
=1/2 * 2
=1
1/6 / 1
=1/6 Ans
2007-06-11 20:32:37
·
answer #10
·
answered by ishita s 2
·
0⤊
0⤋